2012
DOI: 10.1007/s00382-012-1481-2
|View full text |Cite
|
Sign up to set email alerts
|

A verification framework for interannual-to-decadal predictions experiments

Abstract: Decadal predictions have a high profile in the climate science community and beyond, yet very little is known about their skill. Nor is there any agreed protocol for estimating their skill. This paper proposes a sound and coordinated framework for verification of decadal hindcast experiments. The framework is illustrated for decadal hindcasts tailored to meet the requirements and specifications of CMIP5 (Coupled Model Intercomparison Project phase 5). The chosen metrics address key questions about the informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
357
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 284 publications
(367 citation statements)
references
References 56 publications
(66 reference statements)
10
357
0
Order By: Relevance
“…The CRPS is a measure of the integrated squared difference between the cumulative distribution function of the forecasts and the step function located at the observed value (e.g., Goddard et al 2013). A skill score for CRPSs (CRPSS) is calculated in the same way as for MSEs.…”
Section: Methodsmentioning
confidence: 99%
“…The CRPS is a measure of the integrated squared difference between the cumulative distribution function of the forecasts and the step function located at the observed value (e.g., Goddard et al 2013). A skill score for CRPSs (CRPSS) is calculated in the same way as for MSEs.…”
Section: Methodsmentioning
confidence: 99%
“…The quality of the observational record is an inherent uncertainty source, particularly pertaining to variability on decadal and longer time scales.. Limited duration, incomplete spatial coverage, and observational errors hinder our ability to characterize past changes and attribute them to anthropogenic forcing, and limit our ability to evaluate models 65 .…”
Section: Observationsmentioning
confidence: 99%
“…The null hypothesis would state that CE value is equal to one, i.e., RMSE exhibited by hindcast, and historical runs are the same. Readers are encouraged to read Goddard et al [23] for details regarding the non-parametric bootstrap approach in the context of a decadal experiment's verification. The similar performance of historical and hindcast runs as climate predictors are attributed to the efficiency of the ACCA technique because predictor uncertainty is considered as one of the dominant sources of the uncertainty in simulated streamflow [26].…”
Section: Discussionmentioning
confidence: 99%
“…based on the year of SST initialization. Earlier studies found that hindcast runs have the potential of preserving the precipitation and temperature cross-correlation [22] and of predicting long-lead ENSO (El Niño-Southern Oscillation) events [23]. Current study forces BMLS with outputs from multiple hindcast and historical runs to understand the improvement in empirical streamflow simulation from the SST initialization.…”
Section: Introductionmentioning
confidence: 95%